Determination of waves climate in deep waters, o˙shore Peru through calibration of numerical reanalysis and instrumental information - Ramos, Carmela (2017)
To determinate the wave climate in deep water o˙ the Peruvian coast, instrumental data from satellite and buoys was employed to calibrate wave reanalysis from NCEP for the period 1979 to 2017. Wave data was calibrated using an exponential model described by Minguez et al. (2011). The results shows correlation coe°cient values between 0.7 to 0.9, also BIAS and RMSE showed acceptable values, which indicate a good approximation between both information databases. We have obtained wave information in deep waters which can be used to analyze average an extremely wave regimes to study coastal processes, and study the in˛uence of El NIÑO and La NIÑA phenomenon in the study area. This calibrated wave time series reveals that the average conditions for wave height is around 2 m, with maximum heights over 4 m. De predominant direction is from Southest for the northern and center zones, and South-southwest for southern zone. In other hand, it was observed that during El NIÑO and La NIÑA wave height was incremented in all the control points selected. The wave direction during La NIÑA showed predominant direction from South-southwest, while during El NIÑO was observed predominant direction from Southwest.